2021
DOI: 10.1111/aej.12596
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and association with pulp necrosis and development of apical periodontitis – a review and presentation of two case reports

Abstract: The varicella zoster virus as an aetiological agent for endodontic disease is not a well‐recognised entity despite several published case reports. While advances in DNA molecular analysis techniques (PCR) have contributed to the current understanding of the potential role of the varicella zoster virus in the initiation and progression of endodontic disease, a review indicates a need for ongoing research. Case reports are presented of two female patients with a history of herpes zoster who developed pulp necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The pathological process of CAP is induced by predominantly bacterial pathogens, and studies have reported the contribution of viruses such as: EBV (Jakovljevic et al, 2020), varicella zoster virus (Heithersay and Chew, 2021) and other novel pathogens to the development of periapical inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological process of CAP is induced by predominantly bacterial pathogens, and studies have reported the contribution of viruses such as: EBV (Jakovljevic et al, 2020), varicella zoster virus (Heithersay and Chew, 2021) and other novel pathogens to the development of periapical inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple published case reports of prodromal herpes zoster pain initially misdiagnosed as a primary dental condition with subsequent identification of the correct diagnosis when classical features of zoster reactivation become evident later during the disease [10] [11] [12] [13]. Anatomic and radiographic findings mimicking other more customary odontogenic conditions have also been noted in the dental and endodontic literature [12] [13]. Viral infections such as intraoral VZV have been implicated in the formation of periapical abscesses, though the precise relationship between these two is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%